A critical review of the state-of-the-art on social policy, conflict and peace in the Middle East and North Africa region: Why social policy matters for peace and why it is also not enough - Jawad, Rana; Plagerson, Sophie; Jaskolski, Martina (Elsevier, 2025)
This article critically examines of the current state of knowledge on the conceptual and operational intersections between social policy and peace using a comprehensive desk-based review of the literature in the MENA region. Situating itself within the conceptual framework of positive peace, the paper critically assesses the role of social policy in a diversifying landscape of compounding risks, exacerbated by global climate change, environmental degradation, structural inequality, and state fragility, which negatively affect peace.